Optimization of biodiesel production from jatopha oil using immobilized lipase - Alireza Zarei, 1986-; Nor Aishah Saidina Amin, supervisor; Fakulti Kejuruteraan Kimia (2012)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2012